2017
DOI: 10.3390/ijms18102209
|View full text |Cite
|
Sign up to set email alerts
|

A Summary of New Findings on the Biological Effects of Selenium in Selected Animal Species—A Critical Review

Abstract: Selenium is an essential trace element important for many physiological processes, especially for the functions of immune and reproductive systems, metabolism of thyroid hormones, as well as antioxidant defense. Selenium deficiency is usually manifested by an increased incidence of retention of placenta, metritis, mastitis, aborts, lowering fertility and increased susceptibility to infections. In calves, lambs and kids, the selenium deficiency demonstrates by WMD (white muscle disease), in foals and donkey foa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
121
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(145 citation statements)
references
References 393 publications
2
121
0
13
Order By: Relevance
“…It can regulate the G0/G1 and G 2 /M period to block B51, and activate apoptosis [55]. It was reported that p53 is a microtubule-associated protein that monitors the status of micro-tubes directly [63]. Although PTX could not induce genetic damage, it can induce formation of aneuploidy and triggers p53 response, stabilizes microtubules by promoting the distribution of microtubules, then arresting the cell cycle at G0/G1 and G 2 /M period [64].…”
Section: Discussionmentioning
confidence: 99%
“…It can regulate the G0/G1 and G 2 /M period to block B51, and activate apoptosis [55]. It was reported that p53 is a microtubule-associated protein that monitors the status of micro-tubes directly [63]. Although PTX could not induce genetic damage, it can induce formation of aneuploidy and triggers p53 response, stabilizes microtubules by promoting the distribution of microtubules, then arresting the cell cycle at G0/G1 and G 2 /M period [64].…”
Section: Discussionmentioning
confidence: 99%
“…Selenite absorption is mediated by the formation of SeCys and selenoglutathione, which can then be transported across the enterocyte by corresponding transporters of amino acids and peptides (Vendeland, Deagen, & Whanger, 1992;Vendeland, Deagen, Butler, & Whanger, 1994). In addition, SeMet, despite competing with methionine, is absorbed in large quantities through its transporter, whereas selenate absorption is reduced in the presence of sulfate, and the latter occurs at much higher concentrations (Combs & Combs, 1984;Fairweather-Tait, Collings, & Hurst, 2010;Hosnedlova et al, 2017;Surai & Fisinin, 2016). JFDS-2019-0787 Submitted 5/22/2019, Accepted 7/27/2019.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of sperm function is characterized by the sperm number and motility. Several selenoproteins, including mitochondrial capsule selenoprotein (MCSeP) and selenophosphate synthase (SPS-2) are localized in testicular tissue (5). The antioxidant enzymes such as superoxide dismutase (SOD) and catalase (CAT) contribute to the reduction of ROS.…”
Section: Introductionmentioning
confidence: 99%
“…The deficiency in Se intake, as well as other antioxidants, resulted in a decreased activity of antioxidant capacity and increased the production of free radicals (6). The importance of Se in the body, especially in animal species, is not yet completely comprehensive and more studies on the effects of Se may show a number of new biologically important processes (5). Many studies have been done in animals and the effects of Se supplementation have often been evaluated in combination with other antioxidants, but no valid conclusions have been drawn so far.…”
Section: Introductionmentioning
confidence: 99%